2010
DOI: 10.2478/s11532-009-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

DFT investigation on mechanism of dirhodium tetracarboxylate-catalyzed O-H insertion of diazo compounds with H2O

Abstract: Abstract:The mechanism of the dirhodium tetracarboxylate-catalyzed O-H insertion reaction of diazomethane and methyl diazoacetate with H 2 O has been studied in detail using DFT calculations. The rhodium catalyst and a diazo compound couple to form a rhodiumcarbene complex. Of two reaction pathways of the Rh(II)-carbene complex with H 2 O, the stepwise pathway is more preferable than the concerted one. Formation of a Rh(II) complex-associated oxonium ylide is an exothermal process, and direct decomposition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The sterically bulkier acids could improve the diastereoselectivity, and the electron-donating ligand made the electrophilic carbene species less reactive and thus more selective . Liu, Z. and Liu, J. studied theoretically the mechanism of the dirhodium tetracarboxylate-catalyzed O–H bond insertion reactions of diazomethane and methyl diazoacetate with water . They proposed that the nucleophilic addition proceeded via a Rh­(II)-complex-associated oxonium ylide (not a free oxonium ylide).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sterically bulkier acids could improve the diastereoselectivity, and the electron-donating ligand made the electrophilic carbene species less reactive and thus more selective . Liu, Z. and Liu, J. studied theoretically the mechanism of the dirhodium tetracarboxylate-catalyzed O–H bond insertion reactions of diazomethane and methyl diazoacetate with water . They proposed that the nucleophilic addition proceeded via a Rh­(II)-complex-associated oxonium ylide (not a free oxonium ylide).…”
Section: Introductionmentioning
confidence: 99%
“…7 Liu, Z. and Liu, J. studied theoretically the mechanism of the dirhodium tetracarboxylate-catalyzed O−H bond insertion reactions of diazomethane and methyl diazoacetate with water. 19 They proposed that the nucleophilic addition proceeded via a Rh(II)-complex-associated oxonium ylide (not a free oxonium ylide). The computational study by Yu's group suggested that in neutral dirhodium(II) complexcatalyzed O−H bond insertion, a free-ylide pathway was facilitated, and H 2 O could accelerate the [1,2]-H shift as an proton shuttle.…”
Section: ■ Introductionmentioning
confidence: 99%